Services Analysis of Pedestrian Facility in Office and Business Area: Case Study Jalan Wahid Hasyim, Jakarta - Pelangie, Kissi Rosari; Rifai, Andri Irfan; Yudhistira, Pradana (DAS Institute, 2022)
Jalan Wahid Hasyim is in the heart of Central Jakarta's offices and businesses, with a strategic location and easy access to destinations such as Jalan Thamrin or Tanah Abang Shopping Center; many road users choose to travel through this road. This study was conducted to analyze the level of service provided by pedestrian facilities to pedestrians on Jalan Wahid Hasyim in Jakarta. The index performance analysis method was used to compare the value of satisfaction and the importance of pedestrian facilities in Jalan Wahid Hasyim. The results showed that the average satisfaction index was 3.16, the average interest index was 4.24, and the average gap was -1.08. The most common recommendations were to improve pedestrian safety and comfort on Jalan Wahid Hasyim Jakarta.